Association between polyphenol subclasses and prostate cancer: a systematic review and meta-analysis of observational studies - Huang, Yiping; Wang, Wenyan; Jin, Jianxiang (Frontiers in Nutrition, 2024)
Background: The effect of polyphenol subclasses on prostate cancer (PCA) is controversial. Therefore, the purpose of this study was to investigate the relationship between polyphenol subclasses and PCA incidence. Methods: From the establishment of the database to December 2023, a systematic search was conducted on PubMed, Web of Science, Embase, and Cochrane Library to identify relevant observational studies. The adjusted odds ratio (OR) and corresponding 95% confidence interval (95% CI) were used to assess the association. Results: A total of 38 studies (11 were cohort studies and 27 were case-control studies), composing 824,933 participants, were included in this meta-analysis after excluding irrelevant records. The findings of the study revealed that men who consumed dietary polyphenols had a significantly higher risk of PCA compared to those who never or rarely consumed dietary polyphenols (OR=1.01, p=0.023), especially dietary flavonol (OR=1.05, p=0.042), flavanol (OR=1.03, p=0.026) and anthocyanin (OR=1.06, p=0.001). Neither total nor subclasses of dietary polyphenols have an effect on non-localized or high-grade PCA (OR=1.01, p=0.518). Dietary isoflavones tended to reduce the incidence of local or low-grade PCA, although there was no statistically significant difference (OR=1.00, p=0.081). Regarding serum/plasma polyphenol, total polyphenol (OR=0.95, p=0.002), genistein (OR=0.92, p=0.029) and enterolactone (OR=0.92, p=0.022) can reduce the incidence of PCA. No association was observed between total/subclasses of urinary polyphenols and PCA risk. Conclusion: Polyphenols seem to generally increase the risk of PCA in the male population. The effect of polyphenols on PCA is affected by factors such as polyphenol subclasses, their forms (serum/plasma, urinary, dietary), and PCA-related factors (like PCA stage).